EPISTEMOLOGI ILMU NAHWU: STUDI ILMU TATA BAHASA DALAM PERSPEKTIF FILSAFAT ILMU - Roziqi, Ahmad Khoirur; Bakar, M. Yunus Abu (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2025)
The purpose of this study is to analyze the nature, history, scope, objectives and benefits, and validity of nahwu science in an epistemological perspective so that we know that nahwu science can be called a branch of science that studies the depth of Arabic, because many people still do not know how this science is built. The approach used to research this research is descriptive-qualitative which is literature-based, including library research. Namely, searching for and studying literature that is related to the problems that are the object of this research study, not only based on books but also in journals, magazines, and so on. With an Islamic educational philosophy approach based on library data accompanied by discourse analysis, it was found that nahwu science is a science that studies the structure of Arabic grammar. The scope of the study of nahwu science is an explanation of i'rob, mawaqi'ul i'rob, isbat, nafy, rutbah (taqdim or ta'khir), numbers. This nahwu science is sourced from the Qur'an, hadith, poetry, prose. And the validity of Nahwu is considered correct if it is in accordance with the views of scholars from various schools of thought, such as Basrah, Kufah, Baghdad, and Andalusia.